Russian Higher Education Under the War: Back toward Zero Agency - Yudkevich, Maria (International Higher Education, 2024)
This article briefly describes the changes that the Russian higher education system experiences in curriculum, research, and internationalization at universities in war time. The state’s decisions mainly take form in terms of changing normative documents and rules, and changing the directions and volumes of state funding of education and science.